The relationship between work burnout and job performance of vocational education lecturers in public universities in Nigeria - Edokpolor, James Edomwonyi; Legg-Jack, Dagogo William; Imeokparia, Patience Osebhakhomen (Universitas Mercu Buana Yogyakarta, 2022)
The study explored the relationship between work burnout (WB) dimensions (e.g. emotional exhaustion, cynicism and lack of professional accomplishment) and job performance (JP) components (e.g. task and contextual) of vocational education lecturers (VELs) in universities in Nigeria. The target population of the study were 284 VELs from public universities in Nigeria. The study employed a structured questionnaire for data collection. Pearson correlational Metrix and linear regression with a bootstrap bias-correction technique were applied for the analyses of data. The results shows that WB dimensions (e.g. emotional exhaustion, cynicism and lack of professional accomplishment) do not significantly correlate with JP components (e.g. task and contextual) of VELs. The results provided evidence concerning the relationship between WB dimensions and JP components of VELs. However, WB experienced by VELs has affected their JP. In all, caution must be exercised by university administrators in assigning job responsibilities to lecturers.